Needs Analysis for Mental Health Screening Application Development - Andri Gustiadi; Lazuardi, Lutfan (Media Informasi, 2025)
Background: Mental health is an important issue among university students, with many cases of depression, anxiety, and stress often detected late. Constraints in early identification and reporting require innovative solutions, such as surveillance-based mobile applications to support early detection and treatment of mental health. Purpose: to identify the needs related to the development of mobile applications in supporting mental health surveillance using the Depression Anxiety Stress Scales-21 (DASS-21). Methods: The type of research is qualitative research with interview method. The research was at Health Polytechnic Tasikmalaya in January-April 2024. The number of samples in this study amounted to 3 people. Data collection using interview guidelines. Data analysis using qualitative analysis. Research ethics letter numbers No.EA/3048/KEPK Poltekkes_Sby/V/2024. Results: The results of the needs analysis show that the development of mobile applications in supporting mental health surveillance is needed to help the identification process, store data and accelerate action and have data related to the mental health picture of students. Application development in the form of a mobile health app that is easy to use and access with an android-based that can display results as self-evaluation material, future development can be done as needed. Conclusion: The development of mental health applications has been adjusted to the needs through the needs analysis process at Health Polytechnic of Ministry of Health Tasikmalaya.